Whether the right of pursuit is constitutional property interest protectible against the state - Tešić Nenad (Anali Pravnog Fakulteta u Beogradu)
The author, in this paper, is looking for Ariadne's thread, which would help us to find the way through the legal labyrinth composed of justified reaction of the state in the war against organized crime, from one side and what is considered an appropriate protection of secured creditor's subjective rights, from the other side. He points out that in resolving a dilemma, does the mortgagee have the right to enforce its debt against the Republic of Serbia (right of pursuit), in case if the extended confiscation of property (proceeds of crime) includes subject-matter of mortgage, the court should take into account does the mortgagee know or should know about criminal origins of encumbered assets. The court should evaluate a good faith of the mortgagee, bearing in mind all the circumstances of the case, especially: The moment of a mortgage establishment, i.e. whether the registration of mortgage is prior in time to the initiation of a property freezing procedure; Overall business and other relations between mortgagee and mortgagor, i.e. are these parties associated in any other way? Objective changes in the economic position of mortgagee and mortgagor, i.e.is the security agreement true or simulated, in particular, whether the value of the secured claim actually enhanced the property of the mortgagor and at what consideration.